Thoracic Re-irradiation for Locally Recurrent Lung Cancer - Aktan, Meryem (Asian Pac J Cancer Prev, 2016)
BACKGROUND: Patients with recurrent or progressive lung cancer experience a significant symptom burden, negatively affecting quality of life and reducing life expectancy. Thoracic re-irradiation can be used for palliative treatment to relieve symptoms or as a curative treatment. METHODS: Using patient charts, we identified and reviewed 28 cases that had received palliative thoracic re-irradiation for recurrent lung cancer. RESULTS: Before re-irradiation, 32% of patients had stage III non-small cell lung cancer and six had small cell lung cancer. The median interval between treatments was 18.7 months. Median follow-up was 31.2 months from the initial radiotherapy and 5 months after re-irradiation. A better performance status before re-irradiation (<80 vs >80, p=0.09) and a lower overlap 90% isodose (<70 vs >70, p=0.09) showed trends toward improved survival. Grade 1-2 toxicity from re-irradiation was recorded in 12/28 patients, and no grade 3 or 4 acute toxicity was encountered. CONCLUSION: The role of palliative treatment in survival is not clear but it can provide symptomatic relief in patients, with no high grade toxicity. Further studies with greater patient numbers and longer follow-up times should facilitate determination of the role of this treatment in toxicity and effects on survival.